Sustainable Bridge Construction - Methods to reduce the climate footprint from concrete slab frame bridges - Alzokani, Mohamad Omar (My University, 2022)
Greenhouse gas emissions threaten our climate by contributing to global warming. Furthermore, infrastructure and bridge construction are associated with a significant part of these emissions. Considering the Swedish Transport Administration’s long-term goals to reach climate neutrality by 2045, the potential for affecting the climate footprint from bridge structures should be investigated, which is considered significantly high throughout its life cycle. The study investigates the carbon dioxide CO2 emissions from the structural parts for one of Sweden's most common bridge types, the slab frame bridge. The study indicates the emissions from the material production and transportation phases, to achieve the study's purpose, a case study has been carried out on slab frame bridge 100-140-1 in Halvor’s link. A comparative analysis has been conducted for various concrete and reinforcement products, where optimised alternatives have been investigated to promote sustainable material selection. After that, the study analyses the possibility of using environmentally friendly products that initially do not serve the exact required strength and exposure classes in bridge design. Finally, to promote sustainable decision-making, the study discusses the importance of implementing preliminary climate impact results at the early stages of the design. The life cycle analysis for the bridge's structural parts and the comparative analysis showed the possibility of reducing a significant amount of CO2 emissions by promoting more sustainable material selection. The investigations showed that it is possible to use other environmentally friendly products only if it is possible to modify the products to fulfil the exact bridge requirements i.g. strength- and exposure classes. Implementing preliminary climate impact results at the early design phase would enable more sustainable decision-making, in which more optimised designs would be achievable.
Keywords: Slab frame bridge, Life cycle analysis, Carbon dioxide emissions, Material selection, Concrete, Reinforcement.